PENGARUH PEMBERIAN JUS SEMANGKA (CITRULLUS LANATUS) TERHADAP KEJADIAN DELAYED ONSET MUSCLE SORENESS (DOMS) - DINDA ATIKA SURI; CUT MOURISA (LP2MTBM MAKARIOZ, 2020)
Exercise is an activity or a systematic activity and is carried out repeatedly in a certain time and there is a gradual increase inload. Movements that continue to increase without preceding previous sports, or for someone who has just been exercisingand who rarely doing sports can cause a risk of muscle injury. Delayed Onset Muscle Soreness (DOMS) is a condition ofmuscle pain that occurs after doing a type of activity that places an unusual burden on the muscles. This pain usually startsto produce pain in 24-72 hours after exercise or doing sports. The reserch of the study is to find out the effect of watermelonjuice on DOMS cases to UMSU medical faculty students. This is a experimental research using cross sectional. Whereresearchers take samples by simple randomized. The number of research subjects was 24 people consisting of men andwomen and divided into two groups, namely the control group that received a placebo (500 ml of Kurnia syrup with cooltemperatures) and the treatment group given watermelon juice (500 ml with cool temperatures) for 12 times in a month. Theresults obtained from this study that there are significant differences between the control group and the treatment group (p<0.05). There is an effect of watermelon juice (Citrullus lanatus) on the case of Delayed Onset Muscle Soreness (DOMS).